2018
DOI: 10.1186/s12876-018-0739-5
|View full text |Cite
|
Sign up to set email alerts
|

SSH1 expression is associated with gastric cancer progression and predicts a poor prognosis

Abstract: BackgroundSlingshot homolog-1 (SSH1) plays an important role in pathological processes, including in the occurrence and development of tumours. The purpose of this study was to determine whether SSH1 is a key biomarker with prognostic value for survival in patients with gastric cancer.MethodsWe performed immunohistochemistry (IHC) on tissue microarrays containing 100 gastric cancer specimens to evaluate SSH1 protein expression. The association of pathological characteristics with cumulative survival was determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…SSH1-CDK13, SSH1-CDK19, SSH2-EPHB2 were identified with high significance. Slingshot phosphatases have been previously implicated in cancer progression [80,81] and have been known to mediate caspase-modulated actin polymerization towards bacterial clearance upon Legionella infection [82]. In our analysis, Slingshot phosphatase members SSH1, SSH2 were found to be downregulated exclusively in human DCs, while SSH3 was downregulated in both human DCs and MOs.…”
Section: Discussionmentioning
confidence: 54%
“…SSH1-CDK13, SSH1-CDK19, SSH2-EPHB2 were identified with high significance. Slingshot phosphatases have been previously implicated in cancer progression [80,81] and have been known to mediate caspase-modulated actin polymerization towards bacterial clearance upon Legionella infection [82]. In our analysis, Slingshot phosphatase members SSH1, SSH2 were found to be downregulated exclusively in human DCs, while SSH3 was downregulated in both human DCs and MOs.…”
Section: Discussionmentioning
confidence: 54%
“…SSH1-CDK13, SSH1-CDK19, SSH2-EPHB2 were identified with high significance. Slingshot phosphatases have been previously implicated in cancer progression [75,76] and have been known to mediate caspase-modulated actin polymerization towards bacterial clearance upon Legionella infection [77]. In our analysis, Slingshot phosphatase members SSH1, SSH2 were found to be downregulated exclusively in human DCs, while SSH3 was downregulated in both human DCs and MOs.…”
Section: Discussionmentioning
confidence: 56%
“…Wang et al [7] found that the expression of SSH-1 was to be upregulated in pancreatic cancer cell lines with high metastatic potential, and loss of SSH-1 was correlated with an increase in the phosphorylation of cofilin-1 and the inhibition of cancerous cell migration (but not proliferation). Moreover, SSH-1 was also significantly associated with lymph node metastasis in gastric cancer patients, and was an independent predictor of poor clinical outcomes in Maimaiti's research [8]. While, little is known regarding the SSH-1 expression in human stage pT1 bladder UC patients.…”
Section: Discussionmentioning
confidence: 96%
“…Yellow or brown staining indicated SSH-1 positivity. The SSH-1 staining scoring system is based on published research [8]. The intensity of SSH-1 in cancer cells was graded as 0-3, and the number of SSH-1( +) cells was graded as 0-4 according to the percentage of positive cells (0: 0-5%; 1: 6-25%; 2: 26-50%; 3: 51-75%; 4: 76-100%).…”
Section: Ihc and Scoringmentioning
confidence: 99%
See 1 more Smart Citation